2000
DOI: 10.1029/1999gc000023
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic controls on the evolution of Hawaiian ocean island volcanoes

Abstract: [1] Extrinsic parameters that affect the evolution of magmatic systems within and beneath ocean island volcanoes include physical variables such as confining pressure, which controls magma degassing, and temperature of the underlying lithosphere and crust, which controls magma crystallization during ascent. Other extrinsic parameters are environmental variables coupled to the hydrosphere and atmosphere such as hydrothermal circulation systems and even rainfall. All these extrinsic factors interact with intrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 57 publications
3
35
0
Order By: Relevance
“…Although previous velocity studies suggested that melt might be within the oceanic crust (e.g., Hill and Zucca, 1987;Park et al, 2007), this is the fi rst geophysical observation for magma storage under a Hawaiian volcano in its shield-building phase with a high rate of magma supply. It is consistent with the petrologically inferred crustal reservoir of Loihi, a submarine volcano also in its shield-building phase (Clague and Dixon, 2000). Magma reservoirs in the oceanic crust stand in contrast to deep magma reservoirs at the crust-mantle boundary (15-20 km depth) that are associated with late phases of Hawaiian volcanism (Frey et al, 1990;Clague and Dixon, 2000), when magma supply rates are too low to maintain shallow reservoirs.…”
Section: Discussion and Interpretationsupporting
confidence: 82%
“…Although previous velocity studies suggested that melt might be within the oceanic crust (e.g., Hill and Zucca, 1987;Park et al, 2007), this is the fi rst geophysical observation for magma storage under a Hawaiian volcano in its shield-building phase with a high rate of magma supply. It is consistent with the petrologically inferred crustal reservoir of Loihi, a submarine volcano also in its shield-building phase (Clague and Dixon, 2000). Magma reservoirs in the oceanic crust stand in contrast to deep magma reservoirs at the crust-mantle boundary (15-20 km depth) that are associated with late phases of Hawaiian volcanism (Frey et al, 1990;Clague and Dixon, 2000), when magma supply rates are too low to maintain shallow reservoirs.…”
Section: Discussion and Interpretationsupporting
confidence: 82%
“…In the Hawaiian Islands seismic data revealed a 200 km wide, 3 km thick transition zone in the lowermost crust and uppermost mantle beneath Oahu, which was interpreted as a sill-dominated plutonic complex formed by rising magma (ten Brink and Brocher, 1987). Seismic tomography revealed a large volume of intrusive bodies within the oceanic crust beneath the Louisville hotspot track that were emplaced when the crust was young (∼10 Myr) and warm (Contreras-Reyes et al, 2010). Our data suggest that intracrustal intrusions are common not only for young but also for very old (Jurassic to Cretaceous) oceanic crust.…”
Section: Implications For Endogenous Growthmentioning
confidence: 76%
“…Magma reservoirs are established at an early stage of volcano evolution (Clague and Dixon, 2000;Gudmundsson, 2012). This may be exemplified by Funchal Ridge, a cluster of small (<600 m) seamounts up to 50 km from Madeira.…”
Section: Evolution Of Magma Plumbing Systems Beneath Ocean Island Volmentioning
confidence: 99%
See 1 more Smart Citation
“…Flank seismicity, for example, of the magnitude of the great 1868 Ka'u (M $ 8.0) or the 1975 Kalapana earthquakes (M7.2) would certainly shake the submarine flanks, dislodging precarious slope deposits, but such seismicity accompanies flank sliding and must be ongoing, at least for an extensive period of volcanic evolution. Catastrophic flank collapse of the scale observed here, and documented around the islands, is thought to occur relatively late in the evolution of the volcano [e.g., Moore et al, 1989], and may coincide with unusually energetic volcanic eruptions, perhaps explosive in nature [Clague and Dixon, 2000;McMurtry et al, 1999]. Kilauea volcano has experienced at least two extraordinary phreatomagmatic eruptions within the last 50,000 years, both associated with collapse of the summit caldera, and responsible for massive ash deposits dated at 49 and 23-29 ka [Clague et al, 1995].…”
Section: Collapse Of the Central Flank And Growth Of The Outer Benchmentioning
confidence: 99%